Toxicity and mechanism analysis of microplastics - Liu, Pengjia (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Plastic product the use of plastic product in our daily life led to the potential risk of microplastic exposure and its health outcome. Recently, much research about the toxicity of microplastic in different animals. The result of the toxicity of microplastic in animals may help people find out treatments and assets the environmental effect of the microplastic. This research concludes the experiment of microplastic exposure in different animals and from different pathways, where the animals include the Litopenaeus vannamei, Daphnia manga, Eisenia fetida, zebrafish, human trophoblasts and rats and pathways include cells’s oral exposure to the microplastic. The study of microplastic in Litopenaeus vannamei shows the microplastic may inhibit shrimp’s immunity in recognizing disease-causing molecules. In addition, the mechanism of toxicity of microplastics will also be analyzed. The research of the recent study of microplastic toxicity to human and animals can help researchers to evaluate the further impact of microplastic pollution to ecosystem, and treatment to microplastic exposure.